Safety, Efficacy, and Pharmacokinetics of Combination SARS-CoV-2 Neutralizing Monoclonal Antibodies BMS-986414 (C135-LS) and BMS-986413 (C144-LS) Administered Subcutaneously in Non-Hospitalized Persons with COVID-19 in a Phase 2 Trial - Katya Corado; Kara Chew; Mark Giganti; Ying Mu; Courtney Fletcher; Judith Currier; Eric Daar; David Wohl; Jonathan Li; Carlee Moser; Justin Ritz; Arzhang Javan; et al. (Case Western Reserve University, 2024)
Background: Outpatient COVID-19 monoclonal antibody (mAb) treatment via subcutaneous delivery, if effective, overcomes the logistical burdens of intravenous administration. Methods: ACTIV-2/A5401 was a randomized, masked placebo-controlled platform trial where participants with COVID-19 at low risk for progression were randomized 1:1 to subcutaneously administered BMS-986414 (C135-LS) 200 mg, plus BMS-986413 (C144-LS) 200 mg, (BMS mAbs), or placebo. Coprimary outcomes were time to symptom improvement through 28 days; nasopharyngeal SARS-CoV-2 RNA below the lower limit of quantification (LLoQ) on days 3, 7, or 14; and treatment-emergent grade 3 or higher adverse events (TEAEs) through 28 days. Results: A total of 211 participants (105 BMS mAbs and 106 placebo) initiated study product. Time to symptom improvement favored the active therapy but was not significant (median 8 vs 10 days, P=0.19). There was no significant difference in the proportion with SARS-CoV-2 RNA <LLoQ at day 3 (risk ratio [RR] for BMS mAbs versus placebo: 1.03; 95%CI: 0.80, 1.32), at day 7 (RR: 1.04; 95%CI: 0.94, 1.15), or at day 14 (RR: 1.00; 95%CI: 0.90, 1.12). Fewer grade 3 TEAEs were reported for the BMS mAbs arm than placebo (RR: 0.58 [95%CI: 0.25, 1.32]). Through day 28, there were no deaths, and there were 4 hospitalizations in the BMS mAbs arm versus 3 in the placebo arm. Higher early plasma mAb concentrations were associated with more favorable outcomes. Conclusions: While safe, the BMS mAbs delivered subcutaneously were not effective at treating COVID-19 at low risk for progression. The lack of clinically significant activity may relate to the pharmacokinetics of subcutaneous administration of mAbs.